2009
DOI: 10.1016/j.biopsych.2009.06.021
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Psychotherapy on Neural Responses to Rewards in Major Depression

Abstract: Background Unipolar major depressive disorder (MDD) is characterized by anomalous neurobiological responses to pleasant stimuli, a pattern that may be linked to symptoms of anhedonia. However, the potential for psychotherapy to normalize neurobiological responses to pleasant stimuli has not been evaluated. Methods Twelve adults with and 15 adults without MDD participated in two identical functional magnetic resonance imaging (fMRI) scans that utilized a Wheel of Fortune task. Between scans, MDD outpatients r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
197
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(216 citation statements)
references
References 94 publications
17
197
2
Order By: Relevance
“…As researchers began to focus more specifically on DAergic mechanisms, an increasing number of functional imaging studies have turned to paradigms that assess striatal responses to rewardpredicting cues or reward feedback, both of which have been linked to striatal DA (Ferenczi et al, 2016;Knutson and Gibbs, 2007). These latter approaches have been mostly consistent in their observation of blunted striatal responses to reward outcomes or reward-predicting cues in MDD patients (Dichter et al, 2009;Forbes et al, 2009;Gotlib et al, 2010;Pizzagalli et al, 2009), and these initial findings have been replicated in recent studies with larger patient samples. Indeed, one recent study of over 1500 adolescents found that reduced ventral striatal activity during reward anticipation was associated with clinical or subclinical depression, and that lower ventral striatal activity in non-depressed teens at the time of scanning was predictive of developing depressive symptoms over a 2-year follow-up period (Stringaris et al, 2015).…”
Section: Reduced Motivation and Psychomotor Function In Psychiatric Dmentioning
confidence: 60%
“…As researchers began to focus more specifically on DAergic mechanisms, an increasing number of functional imaging studies have turned to paradigms that assess striatal responses to rewardpredicting cues or reward feedback, both of which have been linked to striatal DA (Ferenczi et al, 2016;Knutson and Gibbs, 2007). These latter approaches have been mostly consistent in their observation of blunted striatal responses to reward outcomes or reward-predicting cues in MDD patients (Dichter et al, 2009;Forbes et al, 2009;Gotlib et al, 2010;Pizzagalli et al, 2009), and these initial findings have been replicated in recent studies with larger patient samples. Indeed, one recent study of over 1500 adolescents found that reduced ventral striatal activity during reward anticipation was associated with clinical or subclinical depression, and that lower ventral striatal activity in non-depressed teens at the time of scanning was predictive of developing depressive symptoms over a 2-year follow-up period (Stringaris et al, 2015).…”
Section: Reduced Motivation and Psychomotor Function In Psychiatric Dmentioning
confidence: 60%
“…The precentral gyrus plays an important role in successful response inhibition, while patients in an acute depressive episode tend to show impaired response inhibition (Schmid et al 2011). Increased activity in the left precental gyrus has been reported in patients following treatment with psychotherapy (Dichter et al 2009). Larisch et al (1997) found significant positive correlations between dopamine (D 2 ) binding changes in the left precentral gyrus and an improvement in depression scores following antidepressant treatment, and the left precentral gyrus shows increased functional connectivity with the orbitofrontal cortex at baseline in subsequent responders to antidepressant treatment relative to non-responders (Lisiecka et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Current treatment for depression includes drugs such as selective serotonin reuptake inhibitors, tricyclic antidepressants and monoamine oxidase inhibitors. They are effective and tolerated well but noncompliance due to slow action, low response, and plethora of side effects are generally observed [10][11][12][13][14][15][16][17] . Also they inhibit sexual behavior [18] .…”
Section: (Details On Page 997)mentioning
confidence: 99%